2020
DOI: 10.1093/rheumatology/keaa072
|View full text |Cite
|
Sign up to set email alerts
|

An international, multicentre, double-blind, randomized study (DISSCO): effect of diacerein vs celecoxib on symptoms in knee osteoarthritis

Abstract: Objective The objective of this study was to investigate whether diacerein has comparable efficacy with celecoxib in pain reduction for treatment in symptomatic knee OA patients. Methods This randomized double-blind multicentre non-inferiority trial evaluated diacerein vs celecoxib treatment in patients with Kellgren–Lawrence grade 2–3 and pain scoring ≥4 (10-cm VAS). Patients were randomized to 6 months of treatment with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…One patient in the diacerein group had three SAEs (abdominal pain, elevated transaminase and gamma-glutamyl transferase, collectively suggestive of hepatitis) which resolved spontaneously following drug withdrawal. 134 …”
Section: Synovitis-driven Endotypementioning
confidence: 99%
“…One patient in the diacerein group had three SAEs (abdominal pain, elevated transaminase and gamma-glutamyl transferase, collectively suggestive of hepatitis) which resolved spontaneously following drug withdrawal. 134 …”
Section: Synovitis-driven Endotypementioning
confidence: 99%
“…The multicenter randomized trial concluded that diacerein was non-inferior to celecoxib. The percentage of patients experiencing joint effusion diminished by half over time, however, without notable discrepancies between the two treatment groups [ 149 ]. In rat synovial cells, diacerein reduced the mRNA levels of inflammatory cytokines (TNFα, IL-1, and IL-6), COX2, cartilage-degrading enzymes (MMP-3 and MMP-13), and ADAMTS-5 in a dose-dependent manner while also raising those of certain anti-inflammatory factors (IL-4 and IL-10).…”
Section: Therapeutic Approach To Synovial Inflammation In Knee Ostmentioning
confidence: 99%
“…For a comprehensive review on such effects, the reader can refer to two recent works that analyzed extensively the antiosteoarthritis properties of diacerein [ 111 , 112 ]. Nonetheless, a very recent clinical trial compared diacerein to celecoxib in patients affected by knee osteoarthritis [ 113 ]. The study reported that more than 350 subjects were randomly treated with diacerein and celecoxib for 6 months.…”
Section: Main Anthraquinones With Therapeutic Propertiesmentioning
confidence: 99%